Evaluating Reading Comprehension Activities of Technical 1 Textbook in Light of CEFR Standards at TVTC Technical Colleges Curriculum and Instruction (TEFL Track) - Alharbi , Sunitan Hejab (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2025)
This research aimed to evaluate the reading comprehension activities in the Technical 1 textbook, the core course for teaching technical English in Saudi technical colleges, according to the Common European Framework of Reference for Languages (CEFR). The goal was to ensure the content aligns with international standards and develops students' proficiency to meet the demands of the modern job market. The researcher employed a descriptive-analytical approach, utilizing an analysis tool based on CEFR standards for reading skills at levels A1 to B2. This tool was applied to all units of both the student textbook and the workbook. The tool underwent peer review by a panel of language and technical training experts to ensure its validity and effectiveness. Holsti's reliability test was also conducted to confirm the consistency of the analysis results. The findings revealed that 77.8% of the CEFR reading standards were fully or partially met. The book's strengths lay in its task design, vocabulary support, and visual use of media. However, weaknesses were observed in fostering learner independence, highlighting a need for improved assessment and feedback mechanisms. The analysis also revealed that the textbook units begin with strong alignment with the lower levels (A1-A2), then the degree of alignment decreases with the higher levels (B1-B2), particularly in tasks requiring analytical thinking and critical evaluation of specialized technical texts. The research recommended several developmental measures, including: Diversifying the used technical texts and introducing realistic work scenarios. Developing flexible, dynamic units that consider the logical progression of task difficulty. Enhancing learners' self-assessment tools and adding formative assessment activities and immediate feedback. Expanding the technical vocabulary through a strategy of repetition and progression, and creating mini-dictionaries related to trainees' specializations.